In situ spectroscopy reveals that microorganisms in different phyla use different electron transfer biomolecules to respire aerobically on soluble iron - Blake, Robert; Anthony, Micah D.; Bates, Jordan D.; Hudson, Theresa; Hunter, Kamilya M.; King, Brionna J.; Landry, Bria L.; Lewis, Megan L.; Painter, Richard G. (Frontiers in Microbiology, 2016)
Absorbance spectra were collected on twelve different live microorganisms, representing six phyla, as they respired aerobically on soluble iron at pH 1.5. A novel integrating cavity absorption meter was employed that permitted accurate absorbance measurements in turbid suspensions that scattered light. Illumination of each microorganism yielded a characteristic spectrum of electrochemically reduced colored prosthetic groups that gradually reoxidized when the limiting ferrous ions were depleted. A total of six different patterns of reduced-minus-oxdized difference spectra were observed. Three different spectra were obtained with members of the Gram-negative eubacteria. Acidithiobacillus, representing Proteobacteria, yielded a spectrum in which cytochromes a and c and a blue copper protein were all prominent. Acidihalobacter, also representing the Proteobacteria, yielded a spectrum in which both cytochrome b and a long-wavelength cytochrome a were clearly visible. Two species of Leptospirillum, representing the Nitrospirae, both yielded spectra that were dominated by an unusuall cytochrome with a reduced peak at 579 nm. Sulfobacillus and Alicyclobacillus, representing the Gram-positive Firmicutes, both yielded spectra dominated by a-type cytochromes. Acidimicrobium and Ferrimicrobium, representing the Gram-postitive Actinobacteria, also yielded spectra dominated by a-type cytochromes. Acidiplasma and Ferroplasma, representing the Euryarchaeota, both yielded spectra dominated by a ba3-type of cytochrome. Metallosphaera and Sulfolobus, representing the Crenarchaeota, both yielded spectra dominated by the same novel cytochrome as that observed in the Nitrospirae and a new, heretofore unrecognized redox-active prosthetic group with a reduced peak at around 485 nm. These observations are consistent with the hypothesis that individual acidophilic microorganisms that respire aerobically on iron utilize one of at least six different types of electron transfer pathways that are characterized by different redox-active prosthetic groups. In situ absorbance spectroscopy is shown to be a useful complement to existing means of investigating the details of energy generation in intact microorganisms under physiological conditions.